Respostas
respondido por:
0
Olá!!
Resolução!!
a)
7x - 3 ← 1° termo
b)
x + 5 - 2x ← 2° termo
c)
7x - 3 = x + 5 - 2x
7x - x + 2x = 5 + 3
6x + 2x = 8
8x = 8
x = 8/8
x = 1
S = { 1 }
Espero ter ajudado!!!
Resolução!!
a)
7x - 3 ← 1° termo
b)
x + 5 - 2x ← 2° termo
c)
7x - 3 = x + 5 - 2x
7x - x + 2x = 5 + 3
6x + 2x = 8
8x = 8
x = 8/8
x = 1
S = { 1 }
Espero ter ajudado!!!
respondido por:
0
Olá, boa noite ☺
Resoluções:
7x - 3 = x + 5 - 2x
a)
7x - 3
b)
x + 5 - 2x
c)
7x - 3 = x + 5 - 2x
7x - x + 2x = 5 + 3
8x = 8
x=8/8
x=1
Bons Estudos :)
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás